Proceedings of the 8th International Driving Symposium on Human Factors in Driver Assessment, Training, and Vehicle Design: Dri 2015
DOI: 10.17077/drivingassessment.1560
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Novice and Experienced Drivers Using the SEEV Model to Predict Attention Allocation at Intersections During Simulated Driving

Abstract: Summary:We compared the eye movements of novice drivers and experienced drivers while they drove a simulated driving scenario that included a number of intersections interspersed with stretches of straight road. The intersections included non-hazard events. Cassavaugh, Bos, McDonald, Gunaratne, & Backs (2013) attempted to model attention allocation of experienced drivers using the SEEV model. Here we compared two SEEV model fits between those experienced drivers and a sample of novice drivers. The first was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Their results showed a high correlation between predicted and observed percentage dwell time. Other studies also showed high correlations between SEEV-predictive and observed dwell time percentages in various types of human-machine interaction tasks [58][59][60][61][62][63].…”
Section: Discussionmentioning
confidence: 97%
“…Their results showed a high correlation between predicted and observed percentage dwell time. Other studies also showed high correlations between SEEV-predictive and observed dwell time percentages in various types of human-machine interaction tasks [58][59][60][61][62][63].…”
Section: Discussionmentioning
confidence: 97%
“…To calculate the model fit, the predicted PDT is correlated with the empirically observed PDT that are collected using eye tracking (Wickens, 2015;Wickens et al, 2003). The model has been validated in different domains, such as aviation (model fit correlations >0.90; Steelman et al, 2011;Wickens et al, 2003;Wickens et al, 2008), driving (model fit correlations range ∼0.75-0.98; Bos et al, 2015;Cassavaugh et al, 2013;Horrey et al, 2006), scrub nursing during surgery (model fit correlations ∼0.70; Koh et al, 2011), and anesthesiology (model fit correlations rage ∼0.72 to ∼0.82; Grundgeiger et al, in press;Grundgeiger, Wurmb, et al, 2020). Wickens (2015) and Wickens et al (2008) argued that a model that only includes expectancy and value (the EV model version) can be used as a gold standard because only these top-down factors should guide the attention allocation of experts.…”
Section: Investigating Visual Attention Allocation During Complex Tasksmentioning
confidence: 99%
“…The SEEV model has been validated in different supervisory control tasks such as flying (Steelman, McCarley, & Wickens, 2011;Wickens et al, 2003;Wickens et al, 2008), driving (Bos et al, 2015;Cassavaugh, Bos, McDonald, Gunaratne, & Backs, 2013;Horrey, Wickens, & Consalus, 2006), and scrub nursing during surgery (Koh, Park, Wickens, Teng Ong, & Noi Chia, 2011). Wickens (2015) describes a static version and a dynamic version for computing the model.…”
Section: The Seev Modelmentioning
confidence: 99%